A sense of distance and movement characteristics of golfers tested without visual feedback of outcomes: Is a putt that feels subjectively good also physically good? - Hasegawa, Yumiko; Okada, Ayako; Fujii, Keisuke (Frontiers in Sports and Active Living, 2022)
For motor tasks that require fine-tuning, such as adjusting the applied force according to the distance to the target, as required for driving and putting in golf, it is important to develop a high degree of sensitivity of one's movement-produced feedback. In previous research focusing on mental representation in golf, this ability to control distance has been called “a sense of distance”. In particular, this study focused on three skills: motor control of the putter head, perception of the impact force, and prediction of the ball's travel distance. However, the relationship between the motor control of the putter head and the error of the outcome estimation is yet to be clarified. The purpose of the present study is two-fold: first, to clarify whether kinematic variation of putter head is correlated with error in estimating the outcome and, second, to quantitatively evaluate the performer's sensations of good and poor performance generated by the ball's impact, for a comparison of the kinematics and impact force of the putter head based on their assessment. Twelve professionals and 12 intermediate amateurs played two distance targets (at 2.4 and 4.8 m) without visual feedback of the outcomes. The kinematics of the putter head, impact force, final ball position, outcome estimation, and subjective assessment were measured. Our results show that the variability in the peak velocity was moderately correlated with the error of the outcome estimation in amateurs' 4.8-m putting task. In addition, amateurs estimated undershoots (overshoots) when they provided worse (better) evaluations. However, the amateurs' trials that were rated as better putts were actually overshoots. These results suggest that the subjectively “good putt” of amateurs was not physically good, and the amateurs putted hard to compensate for the risk of undershoots. However, no remarkable feature of the professional's sense of distance was found. This suggests that professional golfers' sensation is not significantly different from the outcomes that can be physically detected.